Kepastian Hukum Terhadap Diversi Dalam Tindak Pidana Penyertaan (Deelneming) Pada Tingkat Penuntutan - Meilando, Ari; Ismed, Mohamad; Basuki, Basuki (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In Indonesia, the problem of juvenile delinquency has become a serious concern. The delinquency is triggered by intrinsic motivation (inner drive, such as age and position in the family) and extrinsic motivation (external drive, such as family environment, school, social circles, and mass media). Given its broad impact, fair legal efforts are needed that prioritize recovery for children in conflict with the law. One of the approaches implemented is the Diversion system regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This system must be implemented at every level of the criminal justice process, including the prosecution stage. This study focuses on discussing cases of criminal accompaniment (deelneming) involving many child perpetrators. The formulation of the problem raised in this study is How is the application of diversion to criminal accompaniment (deelneming) cases at the prosecution level and how is the legal certainty of the implementation of diversion in criminal accompaniment (deelneming) cases at the prosecution level. In this study, the author uses the theory of punishment and the theory of legal certainty. The research method used is a normative legal approach. This study uses a statute approach and a case approach which in principle originates from primary legal materials consisting of laws and judges' decisions, secondary legal materials consisting of books, research results, articles and tertiary legal materials from libraries, articles and websites. The legal material analysis technique uses grammatical interpretation techniques. The results of this study show that diversion must be implemented by public prosecutors, in addition, public prosecutors who handle child cases must have the following requirements: they must have experience as public prosecutors, have interest, attention, dedication, and understand children's problems, and have attended technical training on child justice. In addition, legal certainty related to Diversion has been clearly regulated in laws and regulations. However, its implementation has not been optimal. The Child Criminal Justice System Law mandates education and training for law enforcers to improve their competence in handling child cases. Unfortunately, the principle of expected legal benefits has not been fully felt by children in conflict with the law. The suggestion in this study is that public prosecutors who handle cases must be public prosecutors who have technical training certification on child justice and that a letter of appointment be made from the Attorney General's Office regarding the case handling team with more than one child perpetrator, the public prosecutor team that handles consists of at least more than 3 (three).